Shear Strength of Soft Clay Reinforced with Single Encased Stone Dust Columns - Hoque, Md. Ikramul; Muzamir, Hasan; Jahan Mim, Nusrat (Penerbit Universiti Teknologi Malaysia, 2023)
The application of stone columns, which can improve the overall carrying capacity of soft clay as well as lessen the settlement of buildings built on it, is among the most widespread ground improvement techniques throughout the globe. The performance of foundation beds is enhanced by their stiffness values and higher strength, which could withstand more of the load applied. Therefore, the cost of construction can be decreased by using recycled stone dust as granular material in vertical granular columns, which can then be strengthened with a singular stone dust column that is covered in geotextile for enhancing soft clay’s overall strength. A further unconfined compression test was performed on remolded specimens of soft kaolin clay measuring 50 mm in diameter and 100 mm in height and mounted with a single encapsulated stone dust column measuring 10 mm and 16 mm in diameter. Test results show that when kaolin is implanted with a single encased stone dust column that has an area replacement ratio of 10.24% and penetration ratios of 0.6, 0.8, and 1.0, the shear strength increases are 51.75%, 74.5%, and 49.20%, respectively. The equivalent shear strength increases are 48.50%, 68.50%, and 43.50% for soft soil treated with a 12.00% area replacement ratio and 0.6, 0.8, and 1.0 penetration ratios, respectively. The diameter and height of the column had an impact on the shear strength parameters, which significantly improved for both encased and non-encased stone dust columns.